The antibacterial activity of berberine against Cutibacterium acnes: its therapeutic potential in inflammatory acne - Sun, Luyao; Yu, Qian; Peng, Fu; Sun, Chen; Wang, Daibo; Pu, Lin; Xiong, Fang; Tian, Yuncai; Peng, Cheng; Zhou, Qinmei (Frontiers in Microbiology, 2024)
Cutibacterium acnes (C. acnes) is a major pathogen implicated in the evolution of acne inflammation. Inhibition of C. acnes-induced inflammation is a prospective acne therapy strategy. Berberine (BBR), a safe and effective natural ingredient, has been proven to exhibit powerful antimicrobial and anti-inflammatory properties. However, the antimicrobial effect of BBR against C. acnes and its role in C. acnes-mediated inflammatory acne have not been explored. The objective of this investigation was to assess the antibacterial activity of BBR against C. acnes and its inhibitory effect on the inflammatory response. The results of in vitro experiments showed that BBR exhibited significant inhibition zones against four C. acnes strains, with MIC and MBC in the range of 6.25-12.5 µg/mL and 12.5-25 µg/mL, respectively. On the bacterial growth curve, the BBR-treated C. acnes exhibited obvious growth inhibition. Transmission electron microscopy (TEM) images indicated that BBR treatment resulted in significant morphological changes in C. acnes. High-content imaging analysis further confirmed that BBR could effectively inhibit the proliferation of C. acnes. The disruption of cell wall and cell membrane structure by BBR treatment was preliminary confirmed according to the leakage of cellular contents such as potassium (K+), magnesium (Mg2+), and alkaline phosphatase (AKP). Furthermore, we found that BBR could reduce the transcript levels of genes associated with peptidoglycan synthesis (murC, murD, mraY, and murG). Meanwhile, we investigated the modulatory ability of BBR on C. acnes-induced skin inflammation in mice. The results showed that BBR effectively reduced the number of C. acnes colonized in mice's ears, thereby alleviating ear swelling and erythema and significantly decreasing ear thickness and weight. In addition, BBR significantly decreased the levels of pro-inflammatory cytokines IL-6, IL-1β, and TNF-α in auricular tissues. These results suggest that BBR has the potential to treat inflammatory acne induced by C. acnes.